2018
DOI: 10.1007/s10545-017-0122-7
|View full text |Cite
|
Sign up to set email alerts
|

A family segregating lethal neonatal coenzyme Q10 deficiency caused by mutations in COQ9

Abstract: Primary CoQ deficiency is a clinically and genetically heterogeneous, autosomal recessive disorder resulting from mutations in genes involved in the synthesis of coenzyme Q (CoQ). To date, mutations in nine proteins required for the biosynthesis of CoQ cause CoQ deficiency with varying clinical presentations. In 2009 the first patient with mutations in COQ9 was reported in an infant with a neonatal-onset, primary CoQ deficiency with multi-system disease. Here we describe four siblings with a previously undiagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…Those differences may reflect the diverse structure and functionality of the mitochondria in different organisms, tissues, and cell types (Vafai & Mootha, 2012). Thus, our study points out the importance of the DMQ 9 /CoQ 9 ratio in the disease phenotype, a fact that is further supported by several evidences: (i) The Coq9 Q95X mouse model has low levels of DMQ 9 and higher levels of CoQ biosynthetic proteins (compared to the Coq9 R239X muse model), and the lifespan is not compromised; (ii) the treatment with ubiquinol-10 in Coq9 R239X mice does not change the DMQ 9 levels and its therapeutic effects are significantly lower than those after b-RA treatment; (iii) the reduction in the DMQ 9 levels in the Coq7 conditional KO mice after b-RA therapy may also contribute to the increased survival observed in this mouse model, although the phenotype of this mouse model is not clear (Wang et al, 2015); and (iv) patients with high levels of DMQ 10 in the samples used for the diagnostic (muscle and/or skin fibroblasts) are associated to severe clinical presentations (Duncan et al, 2009;Freyer et al, 2015;Danhauser et al, 2016;Wang et al, 2017;Smith et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those differences may reflect the diverse structure and functionality of the mitochondria in different organisms, tissues, and cell types (Vafai & Mootha, 2012). Thus, our study points out the importance of the DMQ 9 /CoQ 9 ratio in the disease phenotype, a fact that is further supported by several evidences: (i) The Coq9 Q95X mouse model has low levels of DMQ 9 and higher levels of CoQ biosynthetic proteins (compared to the Coq9 R239X muse model), and the lifespan is not compromised; (ii) the treatment with ubiquinol-10 in Coq9 R239X mice does not change the DMQ 9 levels and its therapeutic effects are significantly lower than those after b-RA treatment; (iii) the reduction in the DMQ 9 levels in the Coq7 conditional KO mice after b-RA therapy may also contribute to the increased survival observed in this mouse model, although the phenotype of this mouse model is not clear (Wang et al, 2015); and (iv) patients with high levels of DMQ 10 in the samples used for the diagnostic (muscle and/or skin fibroblasts) are associated to severe clinical presentations (Duncan et al, 2009;Freyer et al, 2015;Danhauser et al, 2016;Wang et al, 2017;Smith et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic results are greater than those obtained by the classical oral CoQ supplementation because of the decrease of the DMQ/CoQ ratio. Therefore, b-RA should be preferentially considered for the treatment of human CoQ 10 deficiency with accumulation of DMQ 10 , as it has been reported in patients with mutations in COQ9, COQ7, or COQ4 (Duncan et al, 2009;Freyer et al, 2015;Danhauser et al, 2016;Herebian et al, 2017b;Wang et al, 2017;Smith et al, 2018) but also in cells under siRNA knockdown of COQ3, COQ5 and COQ6 (Herebian et al, 2017b). Similar principles could be applied for 3,4-hydroxybenzoic acid, vanillic acid, 2-methyl-4-hydroxybenzoic acid, or 2,3-dimethoxy-4hydroxybenzoic acid in the cases of mutations in COQ6, COQ5, or COQ3 (Heeringa et al, 2011;Yoo et al, 2012;Ribas et al, 2014;Gigante et al, 2017;Herebian et al, 2017a;Pierrel, 2017), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although I have started with congenital lactic acidosis as the earliest onset mitochondrial disease, antenatal mitochondrial disease presentations are increasingly recognized. For example, prenatal presentation has been reported in some of the early‐onset CoQ 10 biosynthesis deficiency syndromes [12,13], defects of mitochondrial ribosomal proteins [14,15] and even in POLG disease [16].…”
Section: Clinical Complexity: Canonical Syndromic Presentations Of Chmentioning
confidence: 99%
“…In 2018, Smith et al [52] reported four siblings, who presented prenatally with an unknown and an ultimately lethal condition characterized by intrauterine growth retardation, oligohydramnios, variable dilated cardiomyopathy, anemia, abnormal appearing kidneys, and autopsy brain findings suggestive of Leigh disease. The patients had the variants c.521+2T>C and c.711+3G>C in COQ9, which cause in-frame deletions (p.Ser127_Arg202del and p. Ala203_Asp237del).…”
Section: Coq9 (Mim614654)mentioning
confidence: 99%